The RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND PERCEPTION WITH THE MOTIVATION OF THE COMMUNITY'S WILLINGNESS TO RECEIVE THE COVID-19 VACCINE IN ANGGRASMANIS VILLAGE, SUB-DISTRICT JENAWI KARANGANYAR REGENCY: HUBUNGAN TINGKAT PENGETAHUAN DAN PERSEPSI DENGAN MOTIVASI KESEDIAAN MASYARAKAT DALAM MENERIMA VAKSIN COVID-19 DI DESA ANGGRASMANIS KECAMATAN JENAWI KABUPATEN KARANGANYAR - Sari, Dian Nur Adkhana; Viani , Dela Okta; Setyaningrum, Niken; Suryati, Suryati (Jurnal Kesehatan Masa Depan, 2022)
ABSTRACT Background : Covid-19 is an infectious disease caused by SARS-Cov-2, the main transmission of the spread of this virus through droplets that come out when coughing and sneezing. One of the efforts made by the government to break the chain of spread of Covid-19 is through vaccines, vaccines are useful to provide protection so as not to be infected or avoid getting seriously ill if infected with Covid-19. The low motivation of the public to carry out the Covid-19 vaccine is due to a lack of knowledge and also the many perceptions in the community that the truth is not clear. Objective : The purpose of this study was to determine the relationship between the level of knowledge and perception with the motivation of people's willingness to receive the Covid-19 vaccine in Anggrasmanis Village, Jenawi District, Karanganyar Regency. Method : This research is a quantitative research (non-experimental). The research design used descriptive correlation with a cross sectional approach. The sample is 290 people. The research instrument used the Covid-19 vaccine knowledge level, Covid-19 vaccine perception and Covid-19 vaccine motivation. Data analysis using Kendall's tau test. Results : The results of the Kendall tau test in this study showed the results (P) < 0.1, namely the p value of 0.000. Thus, it can be concluded that there is a relationship between the level of knowledge and perception with the motivation of the community's willingness to receive the Covid-19 vaccine in Anggrasmanis Village, Jenawi District, Karanganyar Regency. Conclusion : From the results of this study, there is a relationship between the level of knowledge and perception with the motivation of the community's willingness to receive the Covid-19 vaccine in Anggrasmanis Village, Jenawi District, Karanganyar Regency. Keywords : Knowledge Level ; Perception ; Motivation ; Vaccine Covid-19.